Posture modulates the sensitivity of the H-reflex - (:unkn) unknown (SPRINGER, 2018)
The effect of body posture on the human soleus H-reflex via electrical stimulation of the tibial nerve at the popliteal fossa was studied. All parameters that may influence the reflex were controlled stringently. H-reflexes were elicited in three different body postures while keeping the level of background muscle activation to a minimum. The H-reflex curve relative to the M-wave curve did not change significantly in any of the body postures. However, the maximal H-reflex amplitude significantly increased in the prone position compared with the sitting (p = 0.02) and standing positions (p = 0.01). The background level of electrical activity of the soleus muscle did not significantly change during varying body postures. Together, these findings indicate that the effectiveness of the spindle primary afferent synapse on the soleus motor neuron pool changes significantly in prone position as compared to sitting and standing positions. Given that we have controlled the confounding factors excluding the head position relative to the gravity and the receptors that may be differentially activated at varying body postures such as the proprioceptors, it is concluded that the tonic activity from these receptors may presynaptically interfere with the effectiveness of the spindle primary afferent synapses on the soleus motor neurons.
Keywords: PRESYNAPTIC INHIBITION; MOTONEURON EXCITABILITY; VESTIBULAR STIMULATION; HUMAN FOOT; SOLEUS; MUSCLE; AFFERENTS; STANDARDIZATION; THRESHOLD; HUMANS